Effect of naphthalene acetic acid (NAA) as growth regulator along with chelated zinc and iron on the availability of manganese, zinc, copper and iron in Mentha piperita Linn cultivar Kukrail - Prasad, FM; Prakash, Veeru; Jilani, AA; Prasad, S; Thomas, MR; Arnold, R; Robert, KS; Prasad, VK (International Journal of Environment, 2014)
A field experiment was displayed at the research plot of chemistry Department of Allahabad Agricultural Institute Deemed University, Allahabad to study the effect of NAA along with chelated Zinc and Iron on the availability of micronutrients of Mentha piperrita cultivar Kukrail during winter season. It is quite obvious that Mn was influenced significantly by application of NAA and Zn/Fe EDTA through foliar spray. The concentration of Mn increased with increasing levels of NAA with or without application of Zn/Fe EDTA and markedly higher in Mentha plants at 60 ppm NAA with 10ppm Zn/Fe EDTA. The higher concentration of NAA suppressed the uptake of nutrients above 60 ppm. However, the intake of Mn, Zn and Cu was much higher in second year trial with NAA and Zn while Fe obtained higher uptake in first year than that of second year experiment. The application of NAA was found to increase the Cu uptake with increasing doses till 60ppm with or without the incorporation of Zn/Fe and then gradually a fall at higher concentrations. The second cutting value in second year trial was higher than the corresponding year cutting affected by NAA with Zn. The result was found significant over control due to foliar application of NAA and Fe separately in second year experiment. Fe uptake in mint plants grown with different doses of NAA and Fe in second year trial was greater than first year trial. The Fe uptake in menta piperita plants in both trials were found higher over control. But the Fe uptake in mint plants narrowed down above 60ppm of NAA application with or without Zn/Fe EDTA spray. DOI: http://dx.doi.org/10.3126/ije.v3i2.10636 International Journal of the Environment Vol.3(2) 2014: 238-245